1996
DOI: 10.1177/088572889601900105
|View full text |Cite
|
Sign up to set email alerts
|

Transition Practice and Policy Compliance in Ohio: A Survey of Secondary Special Educators

Abstract: In this article the authors examine: (a) statewide implementation of IDEA transition mandates and four other best practices in transition, and (b) factors correlated with their implementation. A survey of transition practices was administered at a statewide meeting for special education supervisors and administrators. Descriptive statistics were used to examine policy and practice implementation and a step-wise multiple regression was used to identify predictors. Respondents reported compliance with an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Teachers who are responsible for transition planning and services often feel unprepared (Blanchett;Knott & Asselin, 1999). This is also the case for transition specialists, who typically derive their transition knowledge from in-service training, conferences, workshops, or experience (Baer, Simmons, & Flexer, 1996;McMahan & Baer, 2001;Wolfe, Boone, & Blanchett, 1998). Consequently, personnel preparation in transition has remained a primary focus of the Research Committee of the Division on Career Development and Transition (DCDT; Blalock, Kleinhammer-Tramill, Morningstar, Wehmeyer, 2003), which has developed a list of competencies for transition personnel based on "research findings on implementing transition services and their implications for promoting personnel competence and leadership" (Blalock, Kochhar-Bryant, et al, 2003, p. 207).…”
Section: Description and Evaluation Of A University-based Transition Endorsement Programmentioning
confidence: 99%
“…Teachers who are responsible for transition planning and services often feel unprepared (Blanchett;Knott & Asselin, 1999). This is also the case for transition specialists, who typically derive their transition knowledge from in-service training, conferences, workshops, or experience (Baer, Simmons, & Flexer, 1996;McMahan & Baer, 2001;Wolfe, Boone, & Blanchett, 1998). Consequently, personnel preparation in transition has remained a primary focus of the Research Committee of the Division on Career Development and Transition (DCDT; Blalock, Kleinhammer-Tramill, Morningstar, Wehmeyer, 2003), which has developed a list of competencies for transition personnel based on "research findings on implementing transition services and their implications for promoting personnel competence and leadership" (Blalock, Kochhar-Bryant, et al, 2003, p. 207).…”
Section: Description and Evaluation Of A University-based Transition Endorsement Programmentioning
confidence: 99%
“…Esta participación de las familias en los procesos de transición es, a su vez, una práctica con extensa literatura que, en la actualidad, resalta la importancia de empoderarlas (DeFur, 2012; Schalock, 2004) para establecer relaciones de colaboración con los y las profesionales (Greene, 2009;Wandry y Pleet, 2012). Las familias perciben que, en muchas ocasiones, no son invitadas a los encuentros de planificación de la transición, por lo menos, de manera consistente (Baer, Simmons y Flexer, 1996) y cuando participan no se sienten tratadas como miembros valorados (DeFur et al, 2001). En la línea hacia esta participación activa, las familias identifican barreras y obstáculos (Bambara et al, 2007) y recalcan lo especialmente estresante que puede ser el periodo de transición (Kim y Turnbull, 2004), donde los cambios y la disminución de los servicios pueden tener implicaciones directas en el bienestar familiar (Blacher, 2001;Blacher y Hatton, 2007).…”
Section: Discussionunclassified
“…We formed questions to reflect best practices through a review of the literature and previous surveys by Baer et al, (1996) and Johnson et al, (1997). Following Johnson's design, each question on the survey was followed by a number of transition practices listed below the main question as indicators of that practice.…”
Section: Instrumentsmentioning
confidence: 99%
“…In collaboration with the leadership of Project Linkages for Individual and Family Empowerment (LIFE), Ohio's systems change project for transition, the authors examined transition policy implementation and best practice in Ohio, as reported by persons developing IEPs for transition-age youth. The authors used varied sources to examine policy and practice including the National Survey of the Implementation of the IDEA Transition Requirements (Johnson et al, 1997), an earlier Ohio survey, Transition Policy Compliance and Best Practice (Baer, Simmons, & Flexer, 1996), and the reauthorization of IDEA.…”
mentioning
confidence: 99%